2021
DOI: 10.3390/ijerph18094446
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Induced Abortion among Chinese Women Seeking Abortion: Two Cross Sectional Studies

Abstract: Background: In China, there were about 9.76 million induced abortions in 2019, 50% of which were repeat abortions. Understanding the tendency of repeat induced abortion and identifying its related factors is needed to develop prevention strategies. Methods: Two hospital-based cross-sectional surveys were conducted from 2005–2007 and 2013–2016 in 24 and 90 hospitals, respectively. The survey included women who sought an induced abortion within 12 weeks of pregnancy. The proportion of repeat induced abortions by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
(28 reference statements)
1
8
1
4
Order By: Relevance
“…The finding from the regression analysis showing that age, residence, ethnicity, and education level are significantly associated with women’s induced abortion experiences confirms the findings of previous studies [ 9 , 12 , 14 , 52 , 53 ], and is consistent with our period and cohort results. The interaction terms in the regression results show that the profile of women who resort to abortion has shifted from well-educated urban women toward rural, less-educated women, contradicting Zheng et al [ 9 ], who found a shift among women resorting to abortion from less-educated rural women to well-educated urban women.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The finding from the regression analysis showing that age, residence, ethnicity, and education level are significantly associated with women’s induced abortion experiences confirms the findings of previous studies [ 9 , 12 , 14 , 52 , 53 ], and is consistent with our period and cohort results. The interaction terms in the regression results show that the profile of women who resort to abortion has shifted from well-educated urban women toward rural, less-educated women, contradicting Zheng et al [ 9 ], who found a shift among women resorting to abortion from less-educated rural women to well-educated urban women.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…The number of births decreased and the proportion of induced abortions rebounded. Regarding age at induced abortion, the number of induced abortions experienced by each woman increases with age; repeat induced abortions occur mainly among women in the older group [ 12 , 17 ]. Although the minimum age at the time of induced abortion is declining [ 32 , 44 ], adolescents’ induced abortions still account for a relatively small proportion, contributing to the upward trend in the average age of women having induced abortions.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations